2012
DOI: 10.1111/j.1748-5967.2012.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of extracts of Hermetia illucens (Diptera: Stratiomyidae) larvae against Gram‐negative bacteria

Abstract: Larvae of the black soldier fly, Hermetia illucens are well‐known fly larvae that inhabit many countries around the world. Antimicrobial agents derived from the larvae may be among the substances that are produced in the body for their survival. This study was carried out to identify the antimicrobial effects of H. illucens larvae that commonly inhabit animal waste and food waste. To evaluate the pharmacological effects of H. illucens larvae extracts, the larvae were extracted by various organic solvents, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 27 publications
4
91
0
4
Order By: Relevance
“…The authors speculated that the antibacterial effect could be due to interaction between the bacterial ribosome or bacterial cell wall and the active substance. In accordance with Choi et al (2012), a reduction was seen for the Gram-negative salmonella and some reduction for thermotolerant coliforms in this study, while no reduction of the Grampositive enterococcus occurred.…”
Section: Hygienic Quality Of Treatment Residuesupporting
confidence: 71%
See 1 more Smart Citation
“…The authors speculated that the antibacterial effect could be due to interaction between the bacterial ribosome or bacterial cell wall and the active substance. In accordance with Choi et al (2012), a reduction was seen for the Gram-negative salmonella and some reduction for thermotolerant coliforms in this study, while no reduction of the Grampositive enterococcus occurred.…”
Section: Hygienic Quality Of Treatment Residuesupporting
confidence: 71%
“…The mechanism behind the reduction of salmonella observed in this study is not known. Choi et al (2012) found that methanol extracts of the black soldier larvae had antibacterial effects on the Gram-negative bacteria studied, but no such effect was seen on the Grampositive ones. The authors speculated that the antibacterial effect could be due to interaction between the bacterial ribosome or bacterial cell wall and the active substance.…”
Section: Hygienic Quality Of Treatment Residuementioning
confidence: 99%
“…Methanol extracts of H. illucens larvae showed antibacterial effects against K. pneumoniae, Neisseria gonorrhoeae and Shigella sonnei. However, these extracts showed no antibacterial effects against Gram-positive bacteria such as B. subtilis, Streptococcus mutans and Sarcina lutea (Choi et al, 2012).…”
Section: Insects Providing Ampsmentioning
confidence: 99%
“…The majority of insect AMPs was isolated from the haemolymph of experimentally infected insects (Dang et al, 2010;Choi et al, 2012;Park et al, 2014Park et al, , 2015Kim et al, 2016), where they are produced in the fat body and in different epithelia. The production of specific AMPs targeted at a specific pathogen may be induced by septic injury by the respective pathogen inducing quick production of antimicrobial peptides (Kim et al, 2016).…”
Section: Production and Expression Of Amps In Insectsmentioning
confidence: 99%
“…It is shown that the antibacterial effect has methanolic extract larvae H. illucens (Choi W. H. et al, 2012). Our studies have shown that the antibacterial activity has melanin suspension in ethanol, which, apparently, due to the solubility of the melanin.…”
Section: Discussionmentioning
confidence: 83%